Innovation Portfolio Management Report (Cambodia, Philippines and Viet Nam) - International Rice Research Institute (2025)
The document showcases innovations developed for Southeast Asian countries, particularly Cambodia, the Philippines, and Viet Nam, under several CGIAR initiatives: Asian Mega-Deltas, Climate Resilience, Plant Health, and Excellence in Agronomy. These CGIAR initiatives aimed to develop and scale up agricultural innovations to address key challenges in food security and environmental sustainability across the region.